2017
DOI: 10.1007/s13205-017-0732-7
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus pumilus strain YSPMK11 as plant growth promoter and bicontrol agent against Sclerotinia sclerotiorum

Abstract: A study was executed in a direction to attenuate Sclerotinia stalk rot (SSR) disease through biocontrol agent and also to enhance crop productivity. Culture filtrate of bacterial strain YSPMK11 inhibited growth of Sclerotinia sclerotiorum in vitro which also exhibited higher plant growth promoting attributes. Interaction studies revealed maximum (81.50%) growth inhibition at 35°C and pH 7.0 after 72 h incubation period with 15% culture filtrate. Based upon 16S rRNA gene sequence strain, YSPMK11 was identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 25 publications
2
16
0
Order By: Relevance
“…Therefore, it is difficult for plants to absorb it directly. Solubilization and mineralization of phosphorus by phosphate solubilizing bacteria such as B. pumilus and B. subtilis has been reported by, Kaushal, Kumar, and Kaushal, (2017), and this study shows that it is an important state that can be achieved. Filter cake compost has been shown to be an effective type of fertilization that promotes phosphate (PO 4 ) solubilization and increases P availability in the soil compared to other types of fertilization.…”
Section: Discussionsupporting
confidence: 55%
“…Therefore, it is difficult for plants to absorb it directly. Solubilization and mineralization of phosphorus by phosphate solubilizing bacteria such as B. pumilus and B. subtilis has been reported by, Kaushal, Kumar, and Kaushal, (2017), and this study shows that it is an important state that can be achieved. Filter cake compost has been shown to be an effective type of fertilization that promotes phosphate (PO 4 ) solubilization and increases P availability in the soil compared to other types of fertilization.…”
Section: Discussionsupporting
confidence: 55%
“…The endophytic microbiome corresponds to the microbes that colonize and reside within the plant tissues [2]. These microbiomes have been exploited as biocontrol agents promoting plant growth and health in various crops [3,4]. Despite this, endophytic microbiota are poorly studied.…”
Section: Introductionmentioning
confidence: 99%
“…These features allow for the occupation of several agroecosystems and are favorable in the development of bioinoculants (Bahadir et al, 2018). In the present study, the isolate B32 was identified as B. pumilus, a species that has been reported as aerobic, as well as having antifungal activity (Kaushal et al, 2017;Cruz et al, 2018). On the other hand, the isolate B116 was identified as B. thuringiensis, a bacterium that normally produces insecticidal crystal proteins against several insects, nematodes, protozoa and mites, being the species most widely used as biopesticide (Chattopadhyay et al, 2004;Sanahuja et al, 2011).…”
Section: Dna Of B119 Strain (Ng)mentioning
confidence: 55%